Comments on localized and integral localized approximations in spherical coordinates. (August 2016) - Gouesbet, Gérard; Lock, James A.
Abstract: Localized approximation procedures are efficient ways to evaluate beam shape coefficients of laser beams, and are particularly useful when other methods are ineffective or inefficient. Comments on these procedures are, however, required in order to help researchers make correct decisions concerning their use. This paper has the flavor of a short review and takes the opportunity to attract the attention of the readers to a required refinement of terminology. Abstract : Highlights: Comments on the use of localized approximations are required and made. A refined terminology is introduced. It is noted that the modified localized approximation, although more accurate, was overlooked. A warning concerning the use of localized approximations for Bessel beams is announced, and will be more extensively discussed elsewhere.